Telecommunications : today's ten most critical telecommunications technologies with a focus on the Internet - Flanagan, Patrick (Computer Technology Research Corp. CharlestonUS, 1997)
Provides relevant technology background and a context for comparing the capabilities of different technologies with the needs of an enterprise. Presents a detailed evaluation of each technology, including the need for the product, its underlying technology, the best uses in a business, product vendors, outlook, and the strategy to employ when using it. Provides an information technology (IT) strategy to address possible implementation.